QuantiFERON‐TB Gold conversion is not uncommon in patients with psoriasis undergoing anti‐tumour necrosis factor‐α therapy. (26th August 2020) - Megna, M.; Ruggiero, A.; Ferrillo, M.; Fabbrocini, G.
Abstract : Linked Article: Ya et al. Br J Dermatol 2020; 182 :800–802 .